Hysteresis Current-Control Strategy for Single-Phase Half-Bridge Shunt Active Power Filters - Komurcugil, Hasan (IEEE, 2013)
This paper presents a hysteresis current-control (HCC) strategy for a single-phase half-bridge shunt active power filter. The half-bridge topology employs two switching devices and two capacitors connected in series. It is shown that the imbalance existing in these capacitor voltages can be successfully eliminated. The HCC strategy is seen to be quite successful in eliminating the unwanted current harmonics. The steady-state and dynamic performance of the HCC strategy has been tested by computer simulations under a diode bridge rectifier load. Simulation results confirm the correct operation of the HCC strategy.
12th International Conference on Environment and Electrical Engineering (EEEIC) -- MAY 05-08, 2013 -- Wroclaw, POLAND
Keywords: shunt active power filter; half-bridge topology; hysteresis current-control